The Antioxidant Role of Artichoke (Cynara scolymus L.) Extract Against Exhaustive Exercise-Induced Oxidative Stress in Young Athletes - S Atashak (Institue of Medicinal Plants, ACECR, 2019)
Background: Strenuous acute exercise induces oxidative stress in the active muscles and circulation, However, consumption of products rich in antioxidants may potentially ameliorate these effects. Objective: The present investigation was conducted to determine the effect of Artichoke (Cynara scolymus L.) extract on oxidative stress and antioxidant defense after aerobic exercise in young athletes. Method: Twenty two subjects received 2400 ml/kg/day Artichoke-leaf extract or placebo capsule for a period of 14 days. All subjects of both groups underwent in acute aerobic exercise before and after 14 days supplementation. Blood samples were collected at pre supplementation, pre exercise, post exercise and 24 hours after exercise. Malondiadehyde (MDA), plasma total antioxidant capacity (FRAP), superoxide dismutase (SOD), and 8-iso-prostaglandin-F2α (8-iso-PGF2α) were measured. Results: The results showed that concentration of MDA and Serum 8-iso-PG F2α, SOD, and plasma total antioxidant significantly increased at immediately and 24 hrs after aerobic exercise (P<0.05). Artichoke supplementation has no effect on concentration of MDA, FRAP and SOD activity immediately after aerobic exercise (P>0.05), but after 24-h of exercise, 8-iso-PG F2α concentration in the group supplement was significantly lower in comparison to placebo group (P=0.002). Conclusion: The results of this study indicated that a single session of strenuous aerobic exercise induces oxidative stress production and increase of antioxidant indices in young athletes. However, further studies are necessary to clarify the exact antioxidant effects of Artichoke extract in athletes.